ffect of Chlorhexidine on Prevention of Local Infection in Temporary Transvenous Pacemaker Catheter Site - mitra siravand; farhad ramezani badr; abolfath alizade diz (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives: The local infection of temporary transvenous pacemaker catheter site is a common hospital acquired infections. This study aimed to assess the effect of the Chlorhexidine Glaciate 2% on prevention of local infection on temporary transvenous pacemaker catheter site. Materials and Methods: In this 7-month randomized controlled trial, 100 patients having temporary transvenous pacemaker were randomly divided into Chlorhexidine (n=52) and Betadine (n=48) groups. Before catheter insertion, the site (femoral vein) was disinfected with related solutions. Insertion site for redness, edema, tenderness and exoda were assessed daily and the dressing was changed using the same solution. Data were analyzed in the SPSS-16. Results: Redness and tenderness were less reported in the Chlorhixidine group (P=0.006). Edema has been occurred in both groups (p>0.05). Exude was not reported in any patient of the groups. Conclusion: The Chlorhexidine Glaciate 2% was more effective than the Beta dine 10% in prevention of temporary transvenous pacemaker catheter site local infection.